2007
DOI: 10.1037/h0100834
|View full text |Cite
|
Sign up to set email alerts
|

Rearing the sad or mad: Differentiating the family environments of depressed versus conduct disordered youth.

Abstract: The following review examines the current literature on parental depression and its characteristic family environment and parenting styles that may be related to the development of Conduct Disorder (CD) or depression in children. A description of the depressed parent and the general effects of depression on parenting and discipline practices are discussed. Studies on the relationship between parental depression and child psychopathology are reviewed. The family environment variables related to CD are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In keeping with our hypotheses, we found that lower levels of maternal depressive symptoms and higher levels of perceived parenting efficacy were significantly associated with higher scores on the POS and lower scores on the NEG parenting subscales of the PPI-P. These results are commensurate with others’ findings that parental depression is related to more withdrawn and critical parenting, and to less positive and supportive parenting (Berg-Nielsen et al, 2002; Jewell & Beyers, 2007; Lovejoy et al, 2000) and provide further evidence of a link between high levels of self-efficacy and positive parenting behaviors (Coleman & Karraker, 2000). In conjunction with previous research, the current results suggest that future research should examine parenting as a potential mediator of the relation between parent and child depression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In keeping with our hypotheses, we found that lower levels of maternal depressive symptoms and higher levels of perceived parenting efficacy were significantly associated with higher scores on the POS and lower scores on the NEG parenting subscales of the PPI-P. These results are commensurate with others’ findings that parental depression is related to more withdrawn and critical parenting, and to less positive and supportive parenting (Berg-Nielsen et al, 2002; Jewell & Beyers, 2007; Lovejoy et al, 2000) and provide further evidence of a link between high levels of self-efficacy and positive parenting behaviors (Coleman & Karraker, 2000). In conjunction with previous research, the current results suggest that future research should examine parenting as a potential mediator of the relation between parent and child depression.…”
Section: Discussionsupporting
confidence: 89%
“…First, factor analyses revealed that both the PPI-C and the PPI-P contained two key factors, one reflecting positive, warm, and supportive parenting and the other reflecting negative, harsh, and critical parenting. These two higher-order dimensions have been central to parent–child research in general and to depression research in particular (Berg-Nielsen et al, 2002; Gerlsma, Snijders, Marijtje, van Duijn, & Emmelkamp, 1997; Jewell & Beyers, 2007; Kim Park et al, 2008; Miller, Cowan, Cowan, Hetherington, & Clingempeel, 1993; O’Hara et al, 2010; Onatsu-Arvilommi, Nurmi, & Aunola, 1998; Stoneman, Brody, & Burke, 1989). The POS and NEG factors closely resembled the two higher-order dimensions that emerged from Hazzard, Christensen, and Margolin (1983) analysis of the Parent Perception Interview, from which the PPI-C and PPI-P were derived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has suggested that family environment is related to several important developmental outcomes in late childhood and early adolescence (Jewell & Beyers, 2008; Olszewski, Kulieke, & Buescher, 1987; Palmer, 2000). Therefore, examining factors that may impact family environment is of particular interest.…”
Section: Introductionmentioning
confidence: 99%